PENILAIAN EKONOMI SUMBERDAYA EKOWISATA Kasus Kotagede (ECONOMIC -VALUATION OF ECOTOURISM RESOURCES -- Case of Kotagede) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT Kotagede, the former capital of Islamic Mataram Kingdom in 16C, is located about 6 kilometers to the south-east of Yogyakarta city, Special Province of Yogyakarta, Indonesia. This area represents the Javanese ideal site and its unique characteristics as preservation and conservation artistic, antiques, classical, archeological buildings with traditional-colonial architectural and Javanese culture. Recently current settlements and urban spaces that are mostly utilized by present society form a living cultural assets that can be recognized as cultural heritage, as significant as monuments likes temples, or other gorgeous individual buildings. The research aims to look for total economic value of ecotourism resources of Kotagede area. Data were obtained from tourists that pay a visit to Kotagede area with the aid of structured questionnaire. In this research, data was processed with linear-logit regression technique. The result indicates that total economic value of ecotourism resources of Kotagede area is about 13,23 billion to 5,39 trillion rupiah. By doing so, it implication is if mishandling in the development of Kotagede, society have to pay high cost of economic.